Introducing GSM system as a communication channel in a Real-Time Remote Control and Monitoring System - Salah Aldeen Ghanem (My University, 2011)
This project proposes a model of using GSM, UMTS System as a part of a Real-Time Remote Control and Monitoring System. Advantages of such a model lies behind the facts of the availability of mobile networks and devices, since there are more than 1000 Mobile network around the globe with over than 3.5 billion subscribers and network coverage of 99% of earths urban areas.  Not mentioning the internet speed, reliability and the cost effectiveness of using mobile packet access feature provided by both GSM and UMTS Networks. Other big advantage is the reliability of mobile networks and their high uptime (usually above 98% uptime), and not forgetting the reliability of internet in general which makes this system valid even for critical applications, One more point is the great potentials of Mobile handhelds and their availability made it more than possible to use them in such application